2019
DOI: 10.1016/j.jaapos.2017.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fiber layer thickness in children with primary congenital glaucoma measured by spectral domain optical coherence tomography

Abstract: To evaluate retinal nerve fiber layer (RNFL) thickness using spectral domain optical coherence tomography (SD-OCT) in a population of children diagnosed with primary congenital glaucoma (PCG). METHODS In this cross-sectional study, 59 eyes of 59 children diagnosed with PCG and 87 eyes of 87 healthy children were evaluated by SD-OCT to measure the RNFL. The global average peripapillary RNFL thickness and sectional RNFL thickness were evaluated in both groups. Differences in global average and sectional thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…In the present study, the observation of SD-OCT measurements of 72 children (19 with paediatric glaucoma, 59 healthy controls) as young as 6 years of age, reveals a significantly reduced pRNFL thickness in glaucoma patients compared to the healthy controls. This is in line with previous results on adults [28] and children [8,29].…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, the observation of SD-OCT measurements of 72 children (19 with paediatric glaucoma, 59 healthy controls) as young as 6 years of age, reveals a significantly reduced pRNFL thickness in glaucoma patients compared to the healthy controls. This is in line with previous results on adults [28] and children [8,29].…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, our analysis may be useful for analyzing cpRNFL data from children excluded from clinical studies because of their eye movement artifacts. 6,7 Further studies will be required to address the application of the methodology and determine the sensitivity/specificity to detect cpRNFL loss when the reference scan is misaligned from the optic disc center.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore subjects with large eye movements or nystagmus are excluded from clinical studies because of artifacts. 6,7 Sophisticated methods have proposed motion artifact correction using multiple orthogonal OCT volumes. [8][9][10][11] Unfortunately, these methods incorporate custom volumetric OCT scanning methods or use hardware that is unavailable on commercial devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have reported the thinning of average pRNFL thickness in all sectors between pediatric glaucoma and controls (25)(26)(27)(28)(29)(30). However, other studies have found that children with glaucoma and normal participants have comparable pRNFL thickness in some regions such as the temporal, nasal, and inferior nasal quadrants (31)(32)(33)(34). Thus, the possible association of each sector between pRNFL thickness and childhood glaucoma remains unclear, which justifies the need for more studies on this issue.…”
Section: Introductionmentioning
confidence: 99%